2003
DOI: 10.1097/01.inf.0000091293.32187.7b
|View full text |Cite
|
Sign up to set email alerts
|

Double blind, randomized, placebo-controlled study of dexamethasone therapy for hematogenous septic arthritis in children

Abstract: A short course of dexamethasone reduced residual joint dysfunction and shortened significantly the duration of symptoms in children with documented hematogenous septic arthritis. These results suggest that a 4-day course of low dose dexamethasone given early benefits children with hematogenous septic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 13 publications
0
64
0
3
Order By: Relevance
“…K kingae infection was also one of the most common causes of childhood septic arthritis in several previous studies 17,18 and the earlier study from our center. 11 By contrast, Odio et al 10 found S aureus to be the most common pathogen. Because penetrance of antibiotics into the joint fluid was not directly evaluated in our study, we could not determine if it was affected by the corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…K kingae infection was also one of the most common causes of childhood septic arthritis in several previous studies 17,18 and the earlier study from our center. 11 By contrast, Odio et al 10 found S aureus to be the most common pathogen. Because penetrance of antibiotics into the joint fluid was not directly evaluated in our study, we could not determine if it was affected by the corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] The results showed that a 4-day course of adjuvant dexamethasone shortened the duration of symptoms and hospital stay and reduced residual dysfunction at the end of therapy. The rationale for the dosing schedule was derived from the Haemophilus influenzae B meningitis protocol 13 ; the use of corticosteroids was prompted by findings of a decrease in synovial T-cell and macrophage levels in animals with septic arthritis treated with dexamethasone and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Septic arthritis continues to be an entity with worrying figures on morbidity and mortality, with scarce information from Latin-American countries [3,4]. The high concurrency of osteomyelitis observed in this series is not surprising [5].…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, it is well known that severity of infection is related to the extent of the inflammatory response of the immune system [2][3][4]. Treatment for bacterial infections with antimicrobials in combination with anti-inflammatory drugs, such as corticosteroids, has been proven to be effective and safe in several randomized controlled trials (RCTs) in patients with bacterial and tuberculous meningitis [5,6], tuberculous pericarditis [7], septic arthritis [8] and septic shock [9]. Furthermore, it has become clear that the beneficial effects of macrolide antibiotics are antiinflammatory in addition to being antibacterial in nature [10].…”
Section: Introductionmentioning
confidence: 99%